2018
DOI: 10.1371/journal.pone.0207304
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly evolving changes and gene loss associated with host switching in Corynebacterium pseudotuberculosis

Abstract: Phylogenomics and genome scale positive selection analyses were performed on 29 Corynebacterium pseudotuberculosis genomes that were isolated from different hosts, including representatives of the Ovis and Equi biovars. A total of 27 genes were identified as undergoing adaptive changes. An analysis of the clades within this species and these biovars, the genes specific to each branch, and the genes responding to selective pressure show clear differences, indicating that adaptation and specialization is occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
(141 reference statements)
1
4
0
Order By: Relevance
“…The main differences among the analyzed genomes were recorded between the biovars equi and ovis. As in other studies, pan-genome analysis proved the absence of these CDS coding for genes connected to nitrate reduction in all genomes of the C. pseudotuberculosis biovar ovis strains as well as the absence of the CRISPR-Cas system [46,47]. Therefore, based on ANI values and the absence of CDS coding for genes connected to nitrate reduction, the strains sequenced in this study belong to the biovar ovis, which also corresponds to their isolation from sheep or goat lesions.…”
Section: Pan-genomic Analysissupporting
confidence: 80%
“…The main differences among the analyzed genomes were recorded between the biovars equi and ovis. As in other studies, pan-genome analysis proved the absence of these CDS coding for genes connected to nitrate reduction in all genomes of the C. pseudotuberculosis biovar ovis strains as well as the absence of the CRISPR-Cas system [46,47]. Therefore, based on ANI values and the absence of CDS coding for genes connected to nitrate reduction, the strains sequenced in this study belong to the biovar ovis, which also corresponds to their isolation from sheep or goat lesions.…”
Section: Pan-genomic Analysissupporting
confidence: 80%
“…Positive selection was also found to be an important driving force for adaptive evolution of Acidiphilium. Genes can be changed by positive selection for fixation of beneficial variants in a population/species over time if they increase survival fitness, which might help fine-tune gene expression in adaption to changing environmental conditions (27)(28)(29)(30). Those genes under positive selection in Acidiphilium were prone to play key multifunctional roles, of which even small adaptive changes in their coding sequences might influence multiple pathways, bringing considerable benefits for survival of microbes during evolution in response to changing global conditions and shifting of niches.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal gene transfer refers to the acquisition of genetic elements from distant lineages for genetic and phenotypic innovations, a process contributing significantly to evolution within challenging environments and during global geologic and/or climatic events (25,26). Positive selection, on the other hand, mediating survival fitness by adaptive mutations, has also been an indispensable driving force in microbial evolution, and recent investigations have shifted from testing selection on individual genes to the entire genomes (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Exploring the complete genome sequences for dozens of CP strains, another study attempted to find additional molecular markers for the Ovis and Equi biovars. Despite the high genomic conservation reported for CP, the authors identified 27 genes undergoing distinct adaptative changes in Ovis and Equi . However, CP biovar classification had not been assured using the genome information, and the present study effectively distinguished the CP biovars based on whole genome analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the high genomic conservation reported for CP, the authors identified 27 genes undergoing distinct adaptative changes in Ovis and Equi. 37 However, CP biovar classification had not been assured using the genome information, and the present study effectively distinguished the CP biovars based on whole genome analysis. Concatenation of the ANI blast and TNA results generated genomic signatures that allowed accurate grouping of the Ovis and Equi biovars (Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%